Refugees in towns: experiences of integration - Jacobsen, K (Refugee Studies Centre, University of Oxford, 2017)
In countries of first asylum, transit and destination it is increasingly towns and cities that are absorbing refugees. We must look at what is happening at a local level to better understand urban integration as a process shared by refugees and host communities alike.